Planning of Photovoltaic (PV) Type Solar Power Plant as An Alternative Energy of the Future in Indonesia - Bambang Harianto; Mochammad Karjadi (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
Indonesia receives a lot of sunlight throughout the year. This then causes large profits to be obtained with the Development of a Solar Power Plant Planning (PLTS) that uses a photovoltaic (PV) system. This research then aims to look at how the use of PV systems as a solar power generation system becomes alternative energy in the future. The approach used in this research is a qualitative approach through a literature study of various previous studies and studies that discuss the planning of PV-type solar PV in Indonesia. This study found that the PLN network can be integrated and benefit PLTS that are on-grid and use solar modules. Then various public facilities with a flat surface and wide enough can be a good enough place to be a PV type PV mini-grid. Then the ratio of power that PLN has issued for PJU is 76.66%, while the ratio of solar panels is 23.3%. Unfortunately, the main ingredients for making PV mini-grid are still imported, which makes it challenging to develop PV-type PV mini-grid.